OP0293 Implementation of the Eular Recommendations for Cardiovascular Risk Management in Germany: Results of A Cross-Sectional Epidemiologic Study. (10th June 2014) - Krüger, K.; Kleinert, S.; Hecker, R.; Wittig, B.M.; Wolff, B.; Müller-Ladner, U.
Abstract : Background: The increased cardiovascular (CV) risk of patients suffering from rheumatoid arthritis (RA) is well documented and can partially be explained by traditional risk factors [1]. Available evidence supports inflammatory arthritis as an independent CV risk factor due to inflammatory nature of the disease. Patients suffering from ankylosing spondylitis (AS) and psoriatic arthritis (PsA) might inherit a similar increased CV risk [1]. Objectives: To compare CV mortality risk in patients suffering from RA, PsA and AS using the (m)SCORE model and investigate the implementation of the EULAR recommendations for CV risk management in clinical practice. Methods: In this cross-sectional study, patients with diagnosis RA, AS or PsA aged older than 40 years were included at rheumatological outpatient centers in Germany during routine visits. The 10-year CV mortality risk was estimated by both the physician and independently scored using the modified SCORE (mSCORE) for patients with RA or SCORE model for PsA and AS. Specifically age, gender, smoking habits, blood pressure and lipid levels (cholesterol and high-density lipoprotein-cholesterol (HDL-c)) were assessed. Documentation also included medication, comorbidities, DAS28 or BASDAI, CV disease, and standard laboratory parameters. Descriptive data analysis was performed without adjusting for confounders. Differences were compared by performing non-parametric Kruskal-Wallis and Mann-Whitney U-tests. Results: After exclusion of patients with existing CV disease, the analysis population included 1.118 patients with RA, 180 with PsA and 190 with AS from 123 centres. CV risk stratification comparing (m)SCORE values between the three disease entities showed a significantly higher risk of CV disease in RA patients which predominantly was due to the multiplication factor adopted from the EULAR recommendations. Using the mSCORE, about one third of all RA patients had a 10 year CV mortality risk of ≥5%, and 9.5% of all RA patients had a mSCORE ≥10%. Analyzing subgroups not adjusted for confounding factors hints that RA patients with high disease activity (DAS 28 >5.1) might be at a higher 10 year CV mortality risk. Physicians' estimates of the 10 year CV mortality risk matched with the risk calculated by the SCORE model in 61.6% of all cases, while in the predominant proportion of mismatches, the physicians' estimates were close to the risk class of the (m)SCORE model. Around 65% of the investigators stated that the EULAR recommendations influence their diagnostic and therapeutic concept and rated the significance of those recommendations with 6.5 points (SD 2.1) on a VAS. Conclusions: EULAR recommendations are well-known and highly valued amongst German rheumatologists facing a considerable number of patients with significant burden of traditional risk factors illustrated by the (m)SCORE model. The CV 10 year mortality risk was comparable across disease entities when not modifying SCORE values for RA patients. References: Peters MJL et al. Ann Rheum Dis 2010, 69: 325-331. Acknowledgements: This study was sponsored by AbbVie. AbbVie contributed to the study design, research, and interpretation of data, writing, reviewing, and approving the publication. The authors determined the final content. No payments were made to the authors for writing this manuscript. We are grateful to Dr. Imma Fischer (Tübingen) for statistical support. Disclosure of Interest: K. Krüger Consultant for: AbbVie Deutschland GmbH & Co. KG, Speakers bureau: AbbVie Deutschland GmbH & Co. KG, S. Kleinert Consultant for: AbbVie Deutschland GmbH & Co. KG, Speakers bureau: AbbVie Deutschland GmbH & Co. KG, R. Hecker Shareholder of: AbbVie Deutschland GmbH & Co. KG, Employee of: AbbVie Deutschland GmbH & Co. KG, B. Wittig Employee of: AbbVie Deutschland GmbH & Co. KG, B. Wolff Shareholder of: AbbVie Deutschland GmbH & Co. KG, Employee of: AbbVie Deutschland GmbH & Co. KG, U. Müller-Ladner Consultant for: AbbVie Deutschland GmbH & Co. KG, Speakers bureau: AbbVie Deutschland GmbH & Co. KG DOI: 10.1136/annrheumdis-2014-eular.1142